2002
DOI: 10.1046/j.1365-2761.2002.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish density and number of infectious fish on the survival of rainbow trout fry, Oncorhynchus mykiss (Walbaum), during epidemics of infectious pancreatic necrosis

Abstract: Two laboratory studies compared the effect of fish density and number of infectious fish on characteristics of survival of rainbow trout fry during controlled epidemics of infectious pancreatic necrosis (IPN). Analyses of hazard functions and survivor functions were used to determine whether peak death rate, time at which the peak death rate occurred and probability of survival to the end of the experiment were associated with fish density and number of infectious fish added (i.e. pathogen concentration). When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Turnbull & Mitchell 1984) but has only been used sparingly in fish health investigations (Dale et al 1997, Park & Reno 2003, Ogut & Reno 2004, Becker et al 2006. Bebak-Williams et al (2002) applied survival analysis to examine the influence of stocking density and pathogen concentration on survival of rainbow trout Oncorhynchus mykiss experimentally challenged with infectious pancreatic necrosis (IPN) virus. The authors used the Kaplan-Meier model to examine changes in risk over time associated with IPN outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Turnbull & Mitchell 1984) but has only been used sparingly in fish health investigations (Dale et al 1997, Park & Reno 2003, Ogut & Reno 2004, Becker et al 2006. Bebak-Williams et al (2002) applied survival analysis to examine the influence of stocking density and pathogen concentration on survival of rainbow trout Oncorhynchus mykiss experimentally challenged with infectious pancreatic necrosis (IPN) virus. The authors used the Kaplan-Meier model to examine changes in risk over time associated with IPN outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis is a relatively new and useful tool used in the analysis of diseasetransmission models in fish research (Bebak-Williams et al 2002, Becker et al 2002, Ramsay et al 2003. These statistical procedures are used for the analysis of data in which the outcome variable of interest is time until an event occurs, with the event defined as any designated experience (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…decreases hematocrit, hemoglobin, total protein in plasma, number of immature erythrocytes and neutrophilus (Khan et al, 1981). Factors infl uencing the colonization of bacteria on fi ns are frequency and rate of tissue damage, water temperature (Turnbull et al, 1998) and fi sh stock size (Mazur et al, 1993;Bebak-Williams et al, 2002). Schneider and Nicholson (1980) found that there is an increasing frequency of bacterial infection occurrance according to decreasing temperature.…”
Section: Bacterial Infectionsmentioning
confidence: 99%